IL-37 a New IL-1 Family Member Emerges as a Key Suppressor of Asthma Mediated by Mast Cells. (3rd April 2017) - Conti, P.; Ronconi, G.; Caraffa, A.; Lessiani, G.; Duraisamy, Kempuraj
ABSTRACT: In 1986, we reported a multiple biological effect of IL-1 including immunological, inflammatory, and tumor killing activity. Since then other IL-1 family cytokines have been discovered, some with inflammatory and other with anti-inflammatory activity. In this review article, we speculate on the possible inhibitory effect of IL-37 in the light of new findings. IL-37, formerly termed IL-1 family member 7 (IL-1F7), binding IL-18 receptor α chain, acts as a cytokine with intracellular as well as extracellular functionality and as a natural inhibitor of immune responses and inflammation. IL-37 inhibits many pro-inflammatory cytokine and increases anti-inflammatory cytokines such as IL-10. Asthma pathogenesis involves multiple cell types including mast cells, which are important cellular constituents of the human innate and adaptive immunity. IL-37 has an impact on inflammatory cytokines generated by mast cells and is beneficial for and protective in asthma. However, the precise mechanism(s), safety, and tolerability of IL-37 are unclear and still remain a mystery. Abbreviations : GBP (Guanylate Binding Proteins); HMGB1 (High Mobility Group Box protein 1); NLRP (Nucleotide-like Receptor Pyrin domain 1); ASC (Apoptosis-associated Speck-like protein containing CARD, Caspase Recruitment Domain); FGF2 (Fibroblast Growth Factor 2).